A Combinational Digital Logic Design Tool for Practice and Assessment in Engineering Education - Rasha Morsi (Journal of Education and Learning (EduLearn), 2016)
As technology advances, computers are being used almost everywhere. In a 2013 US Census report (File and Ryan, 2014), 83.8% (up from 78.9% in 2012) of U.S. households reported owning a computer with 74.4% reporting internet use (73.4% high speed internet). In recent years, the shift in educational technologies has been moving towards gaming, more specifically serious gaming. Although this is an important trend, there is still much to be said about e-learning through a step-by-step interactive process using an online practice tool. This paper presents a detailed description of the Combinational Logic Design Tool (CLDT) (Morsi and Russell (2007). CLDT was designed and developed under the CCLI project, #0737242, funded by the National Science Foundation, which aimed to develop and disseminate a novel online practice tool for on demand review and assessment in Electrical and Computer Engineering education. The paper also reports on a formal assessment conducted in a Digital Logic Design Classroom and presents the results of this assessment.